PSYCHOLOGICAL IMPACT OF THE STORY “SILVERSPOT – THE STORY OF A CROW” BY ERNEST SETON-THOMPSON - Eshonqulova, Nasiba Husniddin qizi (Educational Research in Universal Sciences, 2023)
In this scientific thesis it is analyzed one of Seton’s most popular animal stories, which is entitled “Silverspot – the Story of a Crow” from Seton’s realistic short story collection “Wild Animals I Have Known” (1898) according to its psychological method in literature. Being a realistic animal story, “Silverspot” is divided into three chapters and the setting of the story is Toronto, Ontario, where Seton resided for a few years of his youth. Author symbolizes the old and wise crow as a human as it acts like a man as well as it has psychological impact with its reactions to the human’s actions.